2021
DOI: 10.1002/brb3.2302
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography monitoring and diagnosing retinal changes in multiple sclerosis

Abstract: This study explores the use of optical coherence tomography (OCT) to monitor and diagnose multiple sclerosis (MS). The analysis of reduced total macular volume and peripapillary retinal nerve fiber layer thinning are shown. The severity of these defects increases as MS progresses, reflecting the progressive degeneration of nerve fibers and retinal ganglion cells. The OCT parameters are noninvasive, sensitive indicators that can be used to assess the progression of neurodegeneration and inflammation in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 162 publications
(234 reference statements)
1
5
0
Order By: Relevance
“…Measurement of RGC/IPL complex thickness via OCT allows a direct objective and noninvasive measure of the physical structure of the retina, which can be extrapolated to visual system function. Thinning of the RGC/IPL complex is known to correspond to deterioration of vision, as well as disease progression in MS and associated diseases [41,59,60]. In this study, we observed notable thinning of the RGC/IPL complex in EAE mice when compared to naïve control mice.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Measurement of RGC/IPL complex thickness via OCT allows a direct objective and noninvasive measure of the physical structure of the retina, which can be extrapolated to visual system function. Thinning of the RGC/IPL complex is known to correspond to deterioration of vision, as well as disease progression in MS and associated diseases [41,59,60]. In this study, we observed notable thinning of the RGC/IPL complex in EAE mice when compared to naïve control mice.…”
Section: Discussionsupporting
confidence: 59%
“…These investigations not only hold the potential to enhance our understanding of the interrelation between structural, functional, and imaging parameters in the context of EAE and MS but also offer insights into the feasibility of employing non-invasive visual assessments, particularly OCT, as potential indicators of CNS involvement. OCT is particularly suitable for evaluating the potential treatment effects of new drugs in preclinical settings, as it has been previously used as a primary and secondary clinical outcome [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest an increased prevalence of age-related macular degeneration among patients with MS ( 24 , 25 ). There is a potential interplay between the neurodegenerative processes occurring in MS and the retinal degeneration seen in age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…GCIPL analyses are reported to be superior compared to pRNFL measurements in tracking the early atrophy caused by optic neuritis, being less influenced by the axonal swelling following edema and inflammation [ 15 , 21 ]. Additionally, GCIPL atrophy after optic neuritis can be detected earlier than pRNFL atrophy, at 1 month after onset [ 15 ].…”
Section: Discussionmentioning
confidence: 99%